Human-Centered Sustainable University Model - Rina Djunita Pasaribu; Aris Hartaman; Moh.Riza Sutjipto; Taufan Umbara; Ridwan Purwanadita; Apriani Masfiroh (Jurnal Manajemen Indonesia, 2022)
In Society 5.0, the central concept is Human-Centered and supported by super-smart technology that frees humans from burdened workloads and allows humans to innovate new values ??without limits. All of this results in prosperity for everyone and that is the achievement of the global Sustainable Development Goals (SDGs). The application of this concept must be realized by all stakeholders of the nation, including universities that are responsible for the education of the younger generation. However, the implementation of sustainability university has been very numerous, varied, and there is no clear definition in the literature or practice. This study aims to develop a Human-Centered sustainable model that can be used as a reference in implementation. The research method used is qualitative by conducting library research, interviews and observations. Respondents and objects of interviews and observations are Telkom University’s sustainability teams and programs/ projects. The result of this study is a Human-Centered sustainable university model that is recommended as an implementation reference, not only for Telkom University but also for other universities with similar characteristics. Keywords—Human-Centered; Sustainability; Tridharma; University; Model